Factors affecting feasibility and quality of second‐trimester ultrasound scans in obese pregnant women. (25th December 2012) - Fuchs, F.; Houllier, M.; Voulgaropoulos, A.; Levaillant, J.‐M.; Colmant, C.; Bouyer, J.; Senat, M.‐V.
Abstract : Linked Comment: Ultrasound Obstet Gynecol 2013:41:7 Abstract: Objectives: To evaluate the feasibility of completing in one session a second‐trimester ultrasound scan in obese pregnant women, to compare the quality of images obtained with those of non-obese women and to analyze factors that can improve the completion rate . Methods: This prospective study, from 2009 to 2011, included all obese pregnant women (prepregnancy body mass index (BMI) > 30 kg/m 2 ) who had an ultrasound examination at 20–24 weeks in our department, and a control group of pregnant women with normal BMI (20–24.9 kg/m 2 ) who had the same examination. A single operator reviewed the standardized ultrasound images (three biometric and six to assess key anatomical features) required under French guidelines, to assess their presence, evaluate the quality of all images and score the quality of the six anatomical images. Each image was assessed according to between four and six criteria, each worth one point. We sought excellent quality, defined as the frequency of maximum points for a given image type. The factors associated with completing the scan in one session were evaluated with multivariate logistic regression . Results: The obese group included 223 women and the control group 60; a complete scan in one session was achieved in 70.4% and 81.7% of these, respectively (P = 0.08). The completion rate for each image type was at least 95% in the control group and 90% in the obese group, except for diaphragm and right outflow tract images. Significant factors associated with completing the scan in the multivariate model were: having 10 additional minutes for the scan (P = 0.03), moving the fetus so that the back was in posterior or lateral position (P = 0.01), more experienced sonographer (P = 0.03) and thinner maternal abdominal wall thickness (P = 0.01). Overall, the excellence rate varied from 35% to 92% in the normal BMI group and from 18% to 58% in the obese group, and was significantly lower in the latter for all images except abdominal circumference (P = 0.26) and spine (P = 0.06). Anatomical quality scores were also significantly lower in the obese group (22.3 vs 27.2; P = 0.001 ). Conclusion: Although ultrasound scans of obese pregnant women are feasible, image quality and global anatomical scores are significantly lower among obese than normal‐weight women. However, certain simple improvements may increase fetal visualization .